Nectar-Secreting and Nectarless Epidendrum: Structure of the Inner Floral Spur - Stpiczyńska, Małgorzata; Kamińska, Magdalena; Davies, Kevin L.; Pansarin, Emerson R. (Frontiers in Plant Science, 2018)
Epidendrum, the largest genus of Neotropical orchids, contains both nectar-secreting and nectarless species. Here, we compare the fine structure of the inner floral spur, termed the cuniculus, in nectariferous (E. difforme, E. nocturnum, E. porpax, E. rigidum, E. vesicatum) and seemingly nectarless (E. capricornu, E. ciliare, E. criniferum, E. pseudepidendrum, E. radicans, E. xanthoianthinum) species. This is the first time for such a detailed investigation of cuniculus structure to be undertaken for Epidendrum. Our aim was to characterize features indicative of secretory activity and to ascertain whether flowers presumed to be nectarless produce alternative pollinator food-rewards. The cuniculus is formed by fusion of the basal part of the labellum and column and extends alongside the ovary and transmitting tract. Our study indicates that all investigated species produce nectar or nectar-like secretion to varying degrees, and no alternative pollinator food-rewards were observed. Even though macroscopic investigation of presumed rewardless species failed to reveal the presence of secretion within the cuniculus, close observations of the cells lining the cuniculus by LM, SEM and TEM revealed the presence of cuticular blisters and surface material. Moreover, the similarity of both the thick tangential cell walls (with the exception of E. vesicatum) and organelle complement of cuniculus epidermal cells in both copiously nectariferous species and those producing only small quantities of surface secretion confirmed the presence of secretory activity in species generally regarded to be rewardless. The secretory character was particularly obvious in the cells of the cuniculus of E. nocturnum, but also in E. ciliare, E. radicans and E. xanthoianthinum, since electron-dense cytoplasm and mitochondria, ER and secretory vesicles were abundant. Furthermore, cell wall protuberances occurred in E. nocturnum, which was indicative of intense transmembrane transport. This investigation highlights the need to examine more closely whether Epidendrum spp. considered to lack food-rewards based solely on macroscopic examination really are rewardless and deceptive.